Determination of reference transition temperature of In-RAFMS in ductile brittle transition regime using numerically corrected Master Curve approach. (July 2015) - Tiwari, Abhishek; Avinash, G.; Sunil, Saurav; Singh, R.N.; Ståhle, Per; Chattopadhyay, J.; Chakravartty, J.K.
Graphical abstract: Fracture behaviour of Indian Reduced Activation Ferritic Martensitic Steel (In-RAFMS) is investigated using small specimens in three point bend loading in subzero temperature range of −110 to −150 °C. The transition reference temperature, T 0, is calculated using Master Curve approach. The small specimens resulted in a non-conservative T 0 ( T 0  = −123.5 °C), due to Large Scale Yielding (LSY) condition near crack tip. A numerical correction method was used to transform LSY fracture toughness to equivalent Small Scale Yielding (SSY) value. The numerical correction method was simulated using ABAQUS and implemented on two datasets, (1) given by Sokolov et al. and (2) by SCK.CEN Belgium Nuclear Research Centre. The correction method was found to be efficient in predicting the T 0 for these two datasets and hence was used on In-RAFMS dataset. The numerically corrected dataset yielded a T 0 of −109 °C which is conservative and close to the values obtained for other RAFMS such as F82H ( T 0  = −105 °C). Master Curve plot for In-RAFMS (a) Uncorrected with T 0  = −123.5 °C (b) Numerically corrected with T 0  = −109 °C. Highlights: Effect of loss of constraint on reference temperature is corrected numerically. Fracture toughness is transformed to equivalent small scale yielding condition. Conservative reference transition temperature is obtained for In-RAFMS dataset. Abstract: The structural material for test blanket module of fusion reactor developed in India is called Indian Reduced Activation Ferritic Martensitic Steel (In-RAFMS). In this study fracture toughness behaviour of In-RAFM steel is investigated using 0.2T bend samples in ductile brittle transition regime. The conventional MC estimates a non-conservative reference transition temperature, T 0, due to Large Scale Yielding (LSY) in small size specimens. Finite element analysis was used to correct the experimental K JC to equivalent Small Scale Yielding (SSY) values. The numerical approach used in this study is based on critical maximum principal stress ( σ ∗ ) – critical stressed volume ( V ∗ ) method.